Hubungan Antara Postur Tubuh Dalam Menggunakan Komputer dengan Keluhan Myofascial Pain Syndrome Pada Karyawan RSU Aminah Blitar - Dian Zahrotul Mila; Dian Pitaloka; Agung Hadi Endaryanto; Ahmad Abdullah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: In the digital era like now, workers always use computers in their work, worker postures that are not in accordance with ergonomics and are carried out for a long time will cause musculoskeletal complaints such as myofascial pain syndrome so that one's performance productivity decreases. Myofascial Pain Syndrome is a description of a chronic or acute pain condition in which connective tissue and muscles are involved (Shah, 2015) which often occurs in the upper trapezius muscle in the form of radiating or local pain.Methods: This type of research uses a quantitative approach with a correlative analytic cross-sectional study with a purposive sampling technique. The population is 53 people. The sample in this study was 30 people, namely Aminah Hospital employees who worked daily in front of the computer and experienced myofascial pain syndrome complaints according to the inclusion and exclusion criteria determined by the researcher. Assessment of work posture using the RULA observation sheet and to determine the diagnosis of myofascial pain syndrome using the modified PMK 65 physiotherapy examination form.Results: The results of this study showed that respondents with moderate risk of changes in posture with the highest level of pain were moderate pain with a total of 19 people (63.3%), who experienced mild pain as many as 4 people (13.3%) and who experienced severe pain as many as 2 people (6.7%). ). Meanwhile, the respondents who experienced the highest risk of changes in posture experienced moderate pain as many as 4 people (13.3%) and mild pain as many as 5 people (16.7%).Conclusion: The conclusion of this study is based on Sommer's d test with a correlation coefficient (r) of 0.104, which means that the relationship between work posture and complaints of myofascial pain syndrome is very weak and the significance value of p is 0.585, if the p value is > 0.05, then Ho is accepted which means there is no a significant correlation or relationship between body posture in using a computer with complaints of myofascial pain syndrome.